Staying in the Crosswalk: A System for Guiding Visually Impaired Pedestrians at Traffic Intersections - Ivanchenko, V. (2009)
Traffic intersections are among the most dangerous parts of a blind or visually impaired person’s travel. Our “Crosswatch” device [4] is a handheld (mobile phone) computer vision system for orienting visually impaired pedestrians to crosswalks, to help users avoid entering the crosswalk in the wrong direction and straying outside of it. This paper describes two new developments in the Crosswatch project: (a) a new computer vision algorithm to locate the more common – but less highly visible – standard “two-stripe” crosswalk pattern marked by two narrow stripes along the borders of the crosswalk; and (b) 3D analysis to estimate crosswalk location relative to the user, to help him/her stay inside the crosswalk (not merely pointing in the correct direction). Experiments with blind subjects using the system demonstrate the feasibility of the approach.